ENGLISH FOR HISTORY STUDENTS. Suport de curs pentru studenții de la specializarea Istorie, anul I - VOICHICI, Oana-Catalina (2017)
English language, one of the most widely spoken languages, is essential in the world oftoday. It is an important tool of communication; it gives students the opportunity of accessingEnglish resources needed to progress in their studies; last, but not least, it may provide betterjob opportunities (sometimes, it is even an essential job requirement). This is why I believethat English language acquisition and the ability to use it are an absolute necessity.English for History Students is an exciting and informative book which addresses allstudents studying History (or those keen on approaching, more or less thoroughly, thisconstantly revealing field of knowledge). It is a language course intended to providelearners with basic historical facts about the United Kingdom and help them learn – andfix in their mind – English terms that are specific to this domain.